Charting the Development of Wealth Inequality in the Netherlands since 1950: an On-going Quest - Coenen, Ann (TSEG - The Low Countries Journal of Social and Economic History, 2017)
This article assesses the value of the available official data series used to map the evolution of Dutch wealth inequality during the latest six decennia. It inventorizes the many methodological and heuristic problems that plague the topic. While we observe that the figures have become less reliable from the sixties onwards, there are a number of indications that total private wealth has, since the eighties, increased at a higher rate than GDP, and that the present level of wealth inequality is slightly higher than the level at the beginning of the nineties. The Netherlands thus appear to join in closer with the Piketty thesis than the Dutch ideal of equality would suggest.